2001
DOI: 10.1002/app.1969
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy of trivalent lanthanum complex as surface modifier of calcium carbonate

Abstract: A complex of trivalent lanthanum stearate with stearin (REC) was used as a surface modifier to treat calcium carbonate, and its efficacy was assessed. The measurement of the viscosity of a CaCO 3 /liquid paraffin suspension demonstrated that REC treatment could considerably improve the dispersion of filler in nonpolar media. The FTIR spectrum analysis revealed that the REC bonded to the CaCO 3 surface not only by physical absorption but also by a chemical reaction. The REC could change the surface properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…LIG1 and LIG2 are dicarboxylic acid and amide-type ligands with coordination numbers of m and n, respectively [10]. Its synthetic method is described in the literature [34]. The diameter and length of a single raw b-NA crystal were tens of nanometers and less than 1 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…LIG1 and LIG2 are dicarboxylic acid and amide-type ligands with coordination numbers of m and n, respectively [10]. Its synthetic method is described in the literature [34]. The diameter and length of a single raw b-NA crystal were tens of nanometers and less than 1 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Feng et al 17 used a complex of trivalent lanthanum stearate with stearin as a surface modifier to treat nCaCO 3 by mechanical mixing, and its efficacy was assessed. They found that the surface properties of nCaCO 3 could be changed.…”
Section: Introductionmentioning
confidence: 99%
“…Possibility of grafted organic layer modification is shown [1]. CaCO 3 as a modification substance is studied in [3][4][5]. CaCO 3 modification with sodium stearate and oleic acid, resulting in greater hydrophobicity, greater stability in nonpolar media and enhanced compatibility with nonpolar matrices, was used to obtain nanocomposites of poly(methylmethacrylate)-CaCO 3 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In [1,2] chemical modification of Ln 3+ -doped LaF 3 and LaPO 4 nanoparticles by organic and organophosphorous acids, 2-aminoethyl phosphate and its derivative is investigated. Authors showed that ligands bond covalently with the ionic crystal surface, caused a solubility of ionic particles in polar aprotic solvents.…”
Section: Introductionmentioning
confidence: 99%